PELAKSANAAN PENGAWASAN PELAYANAN PUBLIK OLEH OMBUDSMAN - Sri Hariati (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
This research aims to determine the implementation of public service monitoring by the ombudsman. The Ombudsman is an independent institution that receives and investigates complaints from victims of public maladministration. Several problem formulations will be discussed, including How the Public Service Administration System is and what is the position of the Ombusdman in the Constitutional System of the Republic of Indonesia. The method used is normative-empirical legal research. Public services according to the Public Service Law include public goods and public services and administrative services regulated in statutory regulations. Article 2 Law no. 37 of 2008 emphasizes that the position of the Ombudsman is a state institution that is independent and does not have organic relationships with other state institutions and government agencies, and in carrying out its duties and authority is free from interference from other powers.